Implikasi Politik Hukum Pengaturan Pertanggungjawaban Kinerja Kepala Daerah Pasca Reformasi - Alan Bayu Aji (Universitas Islam Indonesia, 2017)
This study aims to determine the objective conditions regarding the legal politics of managing the performance accountability of regional heads after the reform. The formulations of the problem include, first, how is the legal politics of the regulation for performance accountability of regional heads after the reform, and second, what is the ideal model of regional head accountability to the regional representative council (DPRD). This research is normative juridical research in which the data used is secondary data in the form of legal materials. In addition, this study uses theories as an analysis tool. The results show that the legal politics of regional head accountability has shifted from DPRD to the central government. The shift is caused by an empirical practice during the enactment of Law No. 22 of 1999 and the domination of DPRD, but the accountability is then shifted to the central government. Domination is also shown by the central government in supervising regional governments, thus minimizing the role of DPRD as a regional representative body with supervisory function. The performance accountability of regional head should be initially presented to DPRD to create equal partnership relations between the two institutions and to place DPRD outside the regional administration element, enabling DPRD to carry out the supervisory function optimally towards directly elected regional heads.Keywords: Legal politics; accountability; regional heads